Impact of Transnational Criminal Organizations on Political, Economic and Social Perspectives of Pakistan - Kashif, Muhammad; Shah, Syed Zafar Ali; Ahmad, Munir (Bulletin of Business and Economics (BBE), 2025)
The study investigates the pervasive impact of Transnational Criminal Organizations (TCOs) on the political, economic, and social perspectives of Pakistan. These criminal syndicates, often operating across borders, exploit weak governance structures and generate significant challenges for the country. Politically, TCOs exacerbate corruption, fuel instability, and undermine state authority through bribery, coercion, and influence over local and national leadership. Economically, these organizations disrupt legitimate markets, facilitate money laundering, and contribute to an underground economy that stifles growth and development. Socially, the presence of TCOs leads to increased violence, lawlessness, and erosion of community structures, contributing to social inequality and insecurity. The study aims to explore the multifaceted effects of TCOs on Pakistan, providing insights into the complexities of governance, security, and development in a globalized world, and offering policy recommendations to mitigate their influence.